TweakIt: Supporting End-User Programmers Who Transmogrify Code - Lau, Samuel; Sarkar, Advait; Srinivasa Ragavan, Sruti; Barik, Titus (Proceedings of the ACM CHI Conference on Human Factors in Computing Systems, 2021)
End-user programmers opportunistically copy-and-paste code snippets from colleagues or the web to accomplish their tasks. Unfortunately, these snippets often don’t work verbatim, so these people — who are non-specialists in the programming language — make guesses and tweak the code to understand and apply it successfully. To support their desired workflow and facilitate tweaking and understanding, we built a prototype tool, TweakIt, that provides users with a familiar live interaction to help them understand, introspect, and reify how different code snippets would transform their data. Through a usability study with 14 data analysts, participants found the tool to be useful to understand the function of otherwise unfamiliar code, to increase their confidence about what the code does, to identify relevant parts of code specific to their task, and to proactively explore and evaluate code. Overall, our participants were enthusiastic about incorporating TweakIt in their own day-to-day work.